Trade Competition and the Decline in Union Organizing: Evidence from Certification Elections - Charles, Kerwin Kofi; Johnson, Matthew S.; Tadjfar, Nagisa (Journal of Labor Economics, 2026)
The long-term decline in US workers’ attempts to organize labor unions accelerated after 2000. We find that the swift rise of imports from China arising from a change in trade policy accounts for nearly all of this post-2000 acceleration: union certification elections decreased substantially among workers in manufacturing industries directly exposed to imports, but also among workers indirectly exposed through their local labor market. Consistent with a simple model of workers’ decision to seek union representation, direct exposure lowered the expected wage gain from unionization, whereas indirect exposure increased the cost of job loss—both of which discourage organizing.